Volcanic rock-confined core-shell nanoreactors as a highly effective and recyclable peroxymonosulfate activator for levofloxacin degradation: Performance, mechanism, and ecotoxicity assessment - Xinxi Fu; Xiangyu Li; Yang Zhong; Shuai Shao; Yonghua Chen; Sha Xie (Environmental Research, 2026)

Synergistic defect and morphology engineering of Mn-doped ZIF-8 for superior ciprofloxacin capture - Jiahao Huang; Xinxi Fu; Xinlu Zhang; Xiao Fu; Qian Liu; Sha Xie (Chemical Engineering Journal, 2026)

MOF derived bimetallic-nanoreactor as peroxymonosulfate activator for highly efficient levofloxacin degradation: Performance and mechanism - Xiangyu Li; Xinxi Fu; Jingdong Wu; Xiao Fu; Jiahao Huang; Yonghua Chen (Chemical Engineering Journal, 2025)

Better waste utilization: Mg-modified biochar from wetland plant waste for phosphorus removal and carbon sequestration - Tingting Wang; Xinxi Fu; Yonghua Chen; Jingdong Wu; Yuanyuan Wang; Honghai Wan; Xiangyu Li; Lizhen Zhao (Journal of Environmental Chemical Engineering, 2024)

The association between artificial light at night and gestational diabetes mellitus: A prospective cohort study from China - Junhao Liao; Chuan Yu; Jiarui Cai; Run Tian; Xingyue Li; Hong Wang; Lin Li; Guishuang Song; Leyao Fu; Xinxi Li; Qiaoyue Ge; Ling Zhang; et al. (Science of The Total Environment, 2024)

Effectiveness of a novel composite filler to enhance phosphorus removal in constructed wetlands - Kaiyuan Gu; Xiongwei Yang; Xing Yan; Chenggang He; Wanchong Mao; Fengkun Xiao; Xiaomeng Wei; Xinxi Fu; Yonglei Jiang (Environmental Science and Pollution Research, 2024)

A thermos-inspired double structural design for efficient and sustainable solar-driven water purification - Xinxian Li; Xinxi Fu; Yonghua Chen; Honghai Wan; Yuanyuan Wang; Hao Wang; Lingying Chen (Journal of Environmental Chemical Engineering, 2023)

Soil moisture regulates warming responses of autumn photosynthetic transition dates in subtropical forests - Yongshuo H. Fu; Xinxi Li; Shouzhi Chen; Zhaofei Wu; Jianrong Su; Xing Li; Shuaifeng Li; Jing Zhang; Jing Tang; Jingfeng Xiao (Global Change Biology, 2022)
Autumn phenology plays a key role in regulating the terrestrial carbon and water balance and their feedbacks to the climate. However, the mechanisms underlying autumn phenology are still poorly understood, especially in subtropical forests. In this study, we extracted the autumn photosynthetic transition dates (APTD) in subtropical China over the period 2003–2017 based on a global, fine‐resolution solar‐induced chlorophyll fluorescence (SIF) dataset (GOSIF) using four fitting methods, and then explored the temporal–spatial variations of APTD and its underlying mechanisms using partial correlation analysis and machine learning methods. We further predicted the APTD shifts under future climate warming conditions by applying process‐based and machine learning‐based models. We found that the APTD was significantly delayed, with an average rate of 7.7 days per decade, in subtropical China during 2003–2017. Both partial correlation analysis and machine learning methods revealed that soil moisture was the primary driver responsible for the APTD changes in southern subtropical monsoon evergreen forest (SEF) and middle subtropical evergreen forest (MEF), whereas solar radiation controlled the APTD variations in the northern evergreen‐broadleaf deciduous mixed forest (NMF). Combining the effects of temperature, soil moisture and radiation, we found a significantly delayed trend in APTD during the 2030–2100 period, but the trend amplitude (0.8 days per decade) was much weaker than that over 2003–2017. In addition, we found that machine learning methods outperformed process‐based models in projecting APTD. Our findings generate from different methods highlight that soil moisture is one of the key players in determining autumn photosynthetic phenological processes in subtropical forests. To comprehensively understand autumn phenological processes, in‐situ manipulative experiments are urgently needed to quantify the contributions of different environmental and physiological factors in regulating plants' response to ongoing climate change.

Decreasing control of precipitation on grassland spring phenology in temperate China - Yongshuo H. Fu; Xuancheng Zhou; Xinxi Li; Yaru Zhang; Xiaojun Geng; Fanghua Hao; Xuan Zhang; Heikki Hanninen; Yahui Guo; Hans J. De Boeck (Global Ecology and Biogeography, 2021)
Aim Vegetation phenology is highly sensitive to climate change. The timing of spring phenology in temperate grasslands is regulated primarily by temperature and precipitation. The aim of this study was to determine whether the primary factor regulating vegetation phenology has changed under ongoing climate change and the underlying mechanisms. Location Temperate semi‐dry grasslands in China. Time period 1982–2015. Major taxa studied Temperate grassland. Methods We extracted start of season (SOS) dates using five standard methods from satellite‐derived normalized difference vegetation index (NDVI) data and determined the primary factor regulating spring phenology using partial correlation analysis. Results The SOS date did not change significantly during the entire 1982–2015 study period in these semi‐dry grasslands, but interannual variability increased significantly from the first subperiod [1982–1998, 8.8 ± 1.1 days (mean ± SE )] to the second subperiod (1999–2015, 10.3 ± 1.1 days). Interestingly, we found that the primary factor regulating SOS shifted from precipitation during 1982–1998 to temperature during 1999–2015. Specifically, we found that during the first period, the SOS in 67.5% of the study area was determined by precipitation (mean partial correlation coefficient, r = 0.58 ± 0.16), but during the second period the main regulating factor in 75.0% of the study area was temperature ( r = 0.61 ± 0.14). Main conclusions The change in the primary driver of spring phenology was attributed mainly to significant increases in preseason precipitation. Our study highlights that the response of spring phenology to climatic factors might change under ongoing climate change. This shift should be addressed in phenology models to simulate grassland phenology better, in addition to its impact on carbon and water cycles in future climate conditions.

Progress in plant phenology modeling under global climate change - Yongshuo Fu; Xinxi Li; Xuancheng Zhou; Xiaojun Geng; Yahui Guo; Yaru Zhang (Science China Earth Sciences, 2020)

MiRNA-200a induce cell apoptosis in renal cell carcinoma by directly targeting SIRT1 - Hao Fu; Wenke Song; Xuancai Chen; Tao Guo; Bin Duan; Xinxi Wang; Yachun Tang; Liang Huang; Chi Zhang (Molecular and Cellular Biochemistry, 2018)